Subjective anxiety ratings before and after stressful neurosurgical virtual reality tumor resection task. (3rd June 2015) - Winkler-Schwartz, A; Fares, J; Khalid, B; Baggiani, M; Christie, S; Alotaibi, F; Al-Zharni, G; Sabbagh, A; Azarnoush, H; Werthner, P; Del Maestro, R
Abstract : Background: The availability of virtual reality (VR) surgical simulators affords the opportunity to assess the influence of stress on neurosurgical operative performance in a controlled laboratory environment. This study sought to examine the effect of a stressful VR neurosurgical task on the subjective anxiety ratings of participants with varying levels of surgical expertise. Methods: Twenty four participants comprised of six staff neurosurgeons, six senior neurosurgical residents (PGY4-6), six junior neurosurgical residents (PGY1-3), and six senior medical students took part in a bimanual VR tumor removal task with a component of sudden uncontrollable intra-operative bleeding. State Trait Anxiety Inventory (STAI) questionnaires were completed immediately pre and post the stress stimulus. The STAI questionnaire consisted of six items (calm, tense, upset, relaxed, content and worried) measured on a Likert scale. Results: Significant increases in subjective anxiety ratings were noted in junior residents (p=0.005) and medical students (p=0.025) while no significant changes were observed for staff and senior neurosurgical residents. Conclusions: Staff and senior residents more effectively mitigate stress compared to junior colleagues in a VR operative environment. Further physiological correlates are needed to determine whether this increased anxiety is paralleled by physiological arousal and altered surgical performance.